[2-(1,3-Dithiolan-2-ylidene)-5-(4-methylphenyl)-3-oxopent-4-enoato-κO]triphenyltin(IV) - Wei Fang; Ze-Min Mei (Acta Crystallographica Section E, 2008)
In the title compound, [Sn(C6H5)3(C17H17O3S2)], the SnIV atom adopts a distorted tetrahedral SnC3O geometry. A short intramolecular Sn...O contact of 2.793 (2) Å also occurs.